Loading effects on floating offshore horizontal axis wind turbines in surge motion. (November 2015) - Micallef, Daniel; Sant, Tonio
Abstract: Previous experimental work under controlled conditions on a small scale floating offshore horizontal axis wind turbine has shown an increasing amplitude of the cyclic thrust and power generation against tip speed ratio under the influence of surge motion. A numerical study is performed using an actuator disc Navier Stokes model, a Blade Element Momentum model and a Generalized Dynamic Wake model on the NREL 5 MW reference rotor in order to confirm or reject these observations on a full-scale surging rotor. The hypothesis was confirmed and the underlying reasons for the observed behaviour were studied on the basis of the near wake physics. It was found that the analysis of transient effects such as fatigue cannot be performed without an adequate aerodynamic model of the wake. Characterization of quasi-steady and unsteady regimes may be useful to establish when detailed aerodynamic wake models are necessary. Highlights: We model a rotor in surge motion using an actuator disc approach. The aerodynamic behaviour of the rotor for different tip speed ratios was analysed. In the low tip speed ratio regime, dynamic wake effects are not important. At high tip speed ratios, thrust and power coefficient variations increase. This confirms previous experimental findings.